Everday Life the Literary discourse of modern decades (Literatures of the World: Poetics, Mentality and Spirituality, 2020)
The article analyzes literary critics works studying the phenomenon of everyday life, approaches of defining the term “everyday life”, its structure and methodology in literary discourse. The term “everyday life”, which was introduced by Sigmund Freud in 1901, did not immediately gain popularity in literary studies. It gradually became the subject of interest in the variety of sciences, such as: history, sociology, philosophy, cultural studies and eventually literary studies. Therefore, the problem of “everyday life” phenomenon needs the interdisciplinary approach of its investigation. Every field of science defines this term in its own way. It is quite difficult to develop a universal structure of everyday life that would fit into all historical periods, types of writings and writers’ worldviews. Depending on changes in values, norms of people’s lives and writers’ worldviews, new elements may be added to the structure of everyday life. All the elements of human everyday life can be considered as integral elements of everyday life, hence we tend to believe that everyday life is a dynamic system, which is inherent in historicity. In addition, the concept of everyday life is characterized by temporal and spatial dimensions. The character reveals and fully shows his personality only in the private space. A versatile analysis of the character’s everyday life allows the researcher to penetrate into his character traits and inner world more deeply, to explain his actions and their motives. After all, nothing can reflect the inner world of a person better than the objects by which he fills his living space.Researchers point out that the analysis of everyday life in a literary text is often carried out on the principle of oppositional categories: daily routine - being, weekdays - holidays, spirituality - despirituality. Depending on the semantics of the concept “everyday life”, its synonyms can be the concepts of “daily routine” and “daily life”. Literary researchers do not aim to characterize “everyday life” in theoretical way, but perceive it as a simple and understandable concept.Based on the analysis of the literary critics studies, it is concluded that the complexity of this phenomenon analyzing lies in the great variety and ambiguity of its interpretations.
Keywords: everyday life; lifeworld; structure; mode of life; existence; dynamic system; historicity; methodology; literary studies; discourse